THE IMPACT OF TECHNOLOGY ON ENGLISH LANGUAGE TEACHING - Ismoilova Shodiya; Murodbek Ismoilov (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
This paper explores the evolving role of technology in the instruction of the English language. As digital tools become increasingly widespread in educational settings, their application in English teaching has shown significant influence on learners’ engagement, autonomy, and language acquisition. Drawing upon recent academic findings and practical observations, this article examines how platforms such as learning management systems (LMS), mobile apps, multimedia resources, and virtual communication tools contribute to vocabulary development, listening skills, grammar proficiency, and intercultural awareness. It further considers the limitations and necessary conditions for successful technology integration. The findings suggest that when technology is used purposefully, it enhances learner motivation and supports more effective, individualized learning experiences.[1] [1] Footnote 1: Technology can tailor learning to individual student needs and pace.